QUALITY AND COMPOSITION OF SCELETIUM PLANT MATERIAL FOR USE AS PHYTO-MEDICINES - Patnala, S.; Kanfer, I. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The Sceletium plant has been reported to contain psychoactive alkaloids, specifically mesembrine, mesembrenone, mesembrenol and other related alkaloids. Sceletium is marketed on the internet as dried plant powder that is claimed to have mood elevation and anti-anxiety properties. Furthermore, the plant, locally known as “kougoed” or “œchanna”, is advertised as having increased potency after it has been fermented. The absence of quality control (QC) requirements for potency and purity of herbal preparations is a major concern due to variation in chemical content and composition between samples and some may not even contain the assumed active contents. The present study investigated the quality and composition of five samples of Sceletium tortuosum plant material and two samples of S. emarcidum, obtained from cultivators and which were intended for use as phytomedicines. The results obtained from HPLC analyses of the five Sceletium tortuosum samples showed large variation in the alkaloidal content and composition with only one sample having quantitifiable alkaloids, mesembrine (0.6%) and mesembranol (0.5%) and lower quantities of the minor alkaloids such as mesembrenone and epimesembranol. The S. emarcidum samples showed complete absence of the relevant alkaloids. These results thus reflect a major issue generally associated with herbal products in that there could be phytopharmaceutical products containing species which either are devoid of presumed chemical components such as alkaloids in the case of Sceletium or whose chemical constituents are too low thereby resulting in inappropriate raw material for use as phytomedicines. Acknowledgements: The authors acknowledge the Medical Research Council, South Africa for a post-doctoral fellowship (S Patnala).